Survei Sarana Prasarana Bolabasket di Sekolah Menengah Atas se-Kecamatan Majenang (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to find out how the conditions, status, and categories of basketball facilities and infrastructure in Senior High Schools in Majenang District were. The method in this research is qualitative research. This type of research is a descriptive design. Sources of data in this study are observations, interviews, and documentation (data triangulation). The results showed that the basketball facilities and infrastructure in high schools in Majenang District were owned by the school itself. SMA N 1 Majenang is in good condition in carrying out basketball lessons. SMA Yos Sudarso has complete facilities and infrastructure, but overall, the basketball facilities and infrastructure at SMA Yos Sudarso do not meet government regulations and do not comply with the standards set by FIBA. SMA Muhammadiyan 1 Majenang and SMA Purnama Majenang are categorized as inadequate, both in terms of the number and condition of government regulations and FIBA ​​standards. This study concludes that the basketball facilities and infrastructure owned by SMA N 1 Majenang are by government regulations and FIBA ​​standards. Meanwhile, the facilities and infrastructure owned by SMA Muhammadiyah 1, SMA Purnama, and SMA Yos Sudarso Majenang are still not by government regulations and FIBA ​​standards